Participatory communication : a practical guide - Tufte, Thomas (World Bank working paper ;, 2009)
What do we mean when we say participatory communication? What are the practical implications of working with participatory communication strategies in development and social change processes? What experiences exists in practice that documents that participatory communication adds value to a development project or programme?The aim of this user guide on participatory communication is to provide answers to some of these questions. Many communication practitioners and development workers face obstacles and challenges in their practical work. A participatory communication strategy offers a very sp.